Microscopic Pore–Throat Architecture and Fractal Heterogeneity in Tight Sandstone Reservoirs: Insights from the Denglouku Formation, Xujiaweizi Fault Depression - Zeqiang Wang; Yunfeng Zhang; Yilin Li; Xuntao Yu; Jiapeng Yuan; Botao Huang (Applied Sciences)
The heterogeneity of the microscopic pore structure in tight sandstone reservoirs is a key factor limiting the efficient development of natural gas. This study focuses on the tight sandstone of the Denglouku Formation in the Lower Cretaceous region of the Xujiaweizi Fault Depression in the northern Songliao Basin. This research integrates petrographic thin sections, scanning electron microscopy (SEM), high-pressure mercury intrusion experiments, and fractal models to systematically reveal the pore structure characteristics and the response patterns of fractal dimensions in the reservoir. The results indicate that the Denglouku Formation reservoir is a typical tight sandstone reservoir, with pore types mainly consisting of residual intergranular pores and micropores, and throat types dominated by narrow lamellar and tubular structures. The pore–throat structure in the study area exhibited typical three-segment fractal characteristics, reflecting the complexity and multi-scale heterogeneity of the reservoir’s pore–throat system. The higher the fractal dimension, the poorer the storage performance and permeability. By constructing a multivariate classification model including porosity, permeability, displacement pressure, and sorting coefficient, the reservoir was divided into three categories. The results of this study provide a theoretical basis for quantitative classification evaluation and development strategy optimization of the continental tight sandstone reservoirs.